Diez tesis de bachillerato en psicología de la Universidad Católica sobre fármaco-dependencia - Lerner Stein, Roberto (1986)
Tñe author analizes 10 research studies related to drug abuse done in the Catholic University of Lima. After summarizing each work, a certain number of observations about recent trends are offered.